Locomotive at Caroni Limited - (:unkn) unknown (My University, 2013)
Train engine (locomotive) at Brechin Castle. The administrative offices and the factory can be seen in the background.
Cataloger's title
Keywords: Locomotives -- Trinidad and Tobago; Sugar factories -- Trinidad and Tobago